Detection of anti-Helicobacter pylori antibodies in sera of women with recurrent spontaneous abortion - Rana Saady Abood; Anmar Saady Abood; Ghadah Mohommed Saleh (World Journal of Experimental Biosciences, 2016)
To determine the relationship between Helicobacter pylori infection and reproduction disorder (recurrent spontaneous abortion), twenty women patients who undergo spontaneous abortion during first trimester of pregnancy (20-38) years and have been investigated from 2015/12/1 -2016/3/1 and compared to fifteen healthy individuals. All subjects were carried out to measure anti-H. pylori IgA and anti- H. pylori IgG antibodies by enzyme-linked immunosorbent assay (ELISA). There was significant elevation (p≤ 0.05) in concentration of anti- H. pylori IgG Abs (6.30± 0.99) compared to control group (4.48± 0.61) and IgA Abs (5.42 ± 0.90 U /ml) as compared to control group (3.92 ± 0.41 U/ml). The percentage of H. pylori IgG and IgA was 20% and 25%, respectively. There was high significant (P ≤ 0.01) difference between control and test groups. While, there were no significant differences (P > 0.05) in the concentration of IgA and IgG of H. pylori according to age. These results indicate that infection with H. pylori plays an important role in reproduction disorder of spontaneous abortion.
Keywords: Abortion, Helicobacter pylori, IgA and IgG.